2012
DOI: 10.1155/2012/679345
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Age-Related Changes in Cardiac Autonomic Nervous Function

Abstract: Ageing is associated with changes in cardiac autonomic control as measured by Heart Rate Variability (HRV). Not many studies have explored the influence of gender on age-related changes in cardiac autonomic regulation. This study evaluated the gender differences in age-associated changes in cardiac autonomic nervous activity by assessing HRV using frequency domain analysis of short-term stationary R-R intervals. HRV was studied in healthy males and females ranging in age from 6 to 55 years. Total power and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 22 publications
9
113
1
4
Order By: Relevance
“…Similar observations were e also reported. 10,11 Again, among the other time domain parameters, SDNN have been failed to show any age effect whereas RMSSD were found consistently and significantly decreased in middle age and older people and also showed significant correlation with age in older subjects specially. No published data are available to compare these findings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar observations were e also reported. 10,11 Again, among the other time domain parameters, SDNN have been failed to show any age effect whereas RMSSD were found consistently and significantly decreased in middle age and older people and also showed significant correlation with age in older subjects specially. No published data are available to compare these findings.…”
Section: Discussionmentioning
confidence: 92%
“…[10][11][12][13][14][15][16][17][18][19] Different time domain components of HRV has been used as marker of overall cardiac autonomic activity. The task force guideline for HRV analysis have demonstrated the interpretation of these parameters to understand the status, behavior and the balance between sympathetic and parasympathetic function due to their continuous interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Female gender seems to result in a lower total variability (Vandeput et al 2012), whereas vagal modulation has been found to be similar (Moodithaya & Avadhany, 2012) or higher (Fukusaki et al 2000;Huikuri et al 1996) when compared to men. These differences in HRV are probably caused by lower sympathetic and higher vagal control of the heart in women (Carter et al 2003).…”
Section: Factors Affecting Hrvmentioning
confidence: 87%
“…HRV is known to decline with age (Byrne et al 1996;Fukusaki et al 2000;Moodithaya & Avadhany, 2012). It has been concluded that age-related changes in HFP, reflecting vagal modulation, are primarily mediated by aging per se and not by physiological changes like physical fitness, body composition or blood pressure, which are characteristics of normal aging (Byrne et al 1996;Fukusaki et al 2000).…”
Section: Factors Affecting Hrvmentioning
confidence: 99%
“…Scientific literature do support the difference in autonomic reactivity among gender but not free from conflicting observations. [5,6] Autonomic tone refers to the resting basal discharge or basal activity free from physiological perturbations or challenges. [7] This is in sharp contrast to autonomic reactivity which measures the degree of change or activity of a system in response to a given stimulus.…”
Section: Introductionmentioning
confidence: 99%